An Efficient Meshless Approach to Multi-scale Modeling in the Time-domain - Yu, Yiqiang; Jolani, Farid; Chen, Zhizhang (David) (Applied Computational Electromagnetics Society Journal (ACES), 2022)
An efficient multi-scale approach to meshless modeling of three-dimensional guided wave problems is realized by hybridization of the radial point interpolation method (RPIM) and the unconditionally stable leapfrog alternatingdirection implicit (ADI-) RPIM scheme. In it, the solution domain is regionalized; the leapfrog ADIRPIM is applied to regions with coarse nodal distributions while the original RPIM is applied to the rest of the dense nodal solution domain. With application of the leapfrog ADI scheme, a uniform time-step can now be applied to the entire solution domain without temporal and spatial interpolation between different computational regions. Furthermore, in the proposed scheme, implicit updating of field variables is confined only within the regions of densely-distributed nodes, yielding a significant saving in memory overhead and a further reduction in CPU time in comparison with leapfrog ADI-RPIM and original RPIM, respectively.